The obesity paradox in early and advanced HER2 positive breast cancer: pooled analysis of clinical trial data - Modi, Natansh D. (NPJ Breast Cancer, 2021)
While many studies have evaluated the relationship between BMI and breast cancer outcomes, it is unclear whether this relationship is consistent between early breast cancer (BC) and advanced BC. The study included 5099 patients with HER2 positive early BC (EBC) and 3496 with HER2 positive advanced BC (ABC). In the EBC cohort, higher BMI was associated with worse overall survival (OS) (HR [95% CI]: overweight = 1.30 [1.13–1.51]; obese = 1.37 [1.14–1.64], P = < 0.001), and worse disease-free survival (overweight = 1.10 [0.98–1.24]; obese = 1.20 [1.04–1.39], P = 0.061). In contrast, for the ABC cohort, higher BMI was significantly associated with improved OS (overweight = 0.85 [0.76–0.96]; obese = 0.82 [0.72–0.95], P = 0.014), and progression-free survival (overweight = 0.91 [0.83–1.01]; obese = 0.87 [0.77–0.98], P = 0.034). In this large high-quality dataset, higher BMI was independently associated with worse survival in EBC, paradoxically in ABC higher BMI was independently associated with improved survival.